(untitled) (Bioresearch Communications, 2026)
Algae or seaweed is a known rich natural source of nutritional and medicinal values, associated with its availability along the coastal areas of the world. Meanwhile, marine sources are known to exhibit biologically active natural products, and a few reports have been published on the detection of bioactive compounds from Jania species of coralline red algae in the division Rhodophyta, such as those found on Bangladeshi St. Martin’s Island. Preliminary phytochemical screening of the ethanolic extract showed the presence of glycosides, alkaloids, saponins, and steroids. Although this species exhibited little antioxidant and antimicrobial activity, the cytotoxicity bioassay showed significant findings, which might be considered an indication for further exploration. High-Performance Liquid Chromatography (HPLC), Ultraviolet and visible (UV-Vis) spectroscopy, and Nuclear Magnetic Resonance (NMR) analysis suggest that some active metabolites are present in plants. These results highlight the potential use of Jania species as a promising candidate for drug discovery and development; however, further studies are necessary to identify its bioactive principles and test its pharmacological applications. Bioresearch Commu. 12(1): 2024-2034, 2026 (January)